Ustrój samorządny województwa śląskiego czy autonomia? Spór doktrynalny czy też różne instytucje ustrojowe? - Drogoń, Andrzej (Z Dziejów Prawa [czasopismo zamknięte], 2020)
Legislative competences guaranteed the voivodeship far-reaching independence within the Polish state’s system of government. A fundamental question arises as to what extent the scope of matters defined as self-governing by the constitutional bill of July 15, 1920, mak- ing the Silesian voivodship autonomous, breached the fundamental principles upon which the structure of government was based according to the March Constitution passed eight months later. It is mainly the case of the state’s uniformity. The terms a “self-governing system” and an “autonomous system of government” may be used interchangeably, noting that the binding phrase for a lawyer should be: a system based on self-governing laws, as it derives from statutory terminology. Regardless of which of these terms we are going to use, they will contain in essence, in their semantic layer a broad form of decentralization, perceived as a scope of competences ascribed to a given community and giving a local community vast freedom to realize their most required goals.